The impact of brand identification, brand image, and brand love on brand loyalty: the mediating role of customer value co-creation in hotel customer experience - Wu, Ming-Hsuan (Frontiers in Communication, 2025)
Amid intensifying competition from both traditional hotels and alternative lodging platforms such as Airbnb, building emotional customer–brand connections has become vital in the hospitality industry. This study investigates how hotel brand identity and brand image influence brand love and, subsequently, brand loyalty, with customer value cocreation behaviors as mediating factors. Drawing on social identity theory and social behavior theory, the model incorporates both engagement and citizenship behaviors to explore their respective impacts. Using purposive sampling, a structured questionnaire was administered in Taiwan and yielded 586 valid responses. Structural equation modeling (SEM) confirmed that brand image had a stronger effect on brand love than brand identity. Among the tested behaviors, information searching and advocacy demonstrated significant mediating effects between brand love and loyalty, underscoring their pivotal role in loyalty development. Other behaviors showed limited or nonsignificant influence. The findings emphasize the importance of emotionally driven and proactive cocreation behaviors in hospitality branding, particularly within the context of Taiwan’s digital service transformation. The study offers theoretical contributions to emotional branding and cocreation literature, and provides practical guidance for hospitality managers seeking to foster loyalty through targeted behavioral engagement.